Have you eaten? The long-run impact of the Great Leap Famine on recent trade - Zilong Li; Xi Chen; Zuzanna Studnicka (University College Dublin, UCD School of Economics, 2024)
This paper estimates the long-run transmission of the Great Leap Famine (1959-61) to the current trade of Chinese provinces. Based on the provincial dispersion of famine severity, we find that provinces more severely affected by the famine have smaller food exports compared to non-food exports, even after over forty years. We present several potential channels including food consumption patterns and risk-related domestic bias, to explain the observed lower food exports in those areas that experienced more intense famine. This study adds to the literature on the effects of the Great Leap Famine and contributes to research on the long-term impacts of historical events on trade.
Keywords: F14; N55; N75; O24; Q17; 330; Great Leap Famine; Trade; Instrumental variables; Famine memory